1106. Infectious Etiologies of Acute Gastroenteritis in Children during the First 100 Days Post-Allogeneic Hematopoietic Cell Transplant. (26th November 2018) - Schuster, Jennifer; Johnston, Samantha; Piya, Bhinnata; Dulek, Daniel; Wikswo, Mary E; Browne, Hannah; Vinje, Jan; Payne, Daniel C; Azimi, Parvin H; Selvarangan, Rangaraj; Halasa, Natasha B; Englund, Janet
Abstract: Background: Acute gastroenteritis (AGE) is a frequent sequela in children undergoing hematopoietic cell transplant (HCT). Although rotavirus and norovirus have been implicated as important causes of AGE, the frequency of other pathogens is unknown. Little data exist on longitudinal prevalence of infectious AGE in HCT. Methods: From February 2015 to May 2016, subjects <18 years undergoing allogeneic HCT were enrolled at four CDC-NVSN sites: Oakland, Kansas City, Seattle, and Nashville. Stool samples were collected at enrollment, weekly until discharge or day 100 (whichever occurred earliest), during re-admissions within the first 100 days, and day 100. AGE was defined as unexplained ≥3 episodes diarrhea and/or ≥1 episode vomiting/24 hours. Specimens were tested using Luminex xTAG Gastrointestinal Pathogen Panel (Austin, TX) and real-time PCR for adenovirus, astrovirus, norovirus, and sapovirus. Results: Thirty-one patients were enrolled at four sites (Seattle: 13, Kansas City: 8, Oakland: 6, Nashville: (4) with median age 5 (IQR 3–10) years. Two hundred sixteen samples were obtained with median 7 samples/subject. During the first 100 days, 29 (94%) subjects met the AGE definition. Thirty-six single pathogen detections occurred in 16 (52%) subjects. Clostridium difficile was the most frequent pathogen (Figure 1), with 14 detections in nine patients, all ≥3 years; 50% of detections were asymptomatic. Seven (50%) detections occurred at HCT onset and none received targeted C. difficile therapy. Sapovirus was detected nine times in four patients, with seven (78%) detections associated with AGE symptoms. Rotavirus was detected nine times, during five symptomatic episodes, in three patients. Adenovirus was detected four times in three patients and all were symptomatic. Conclusion: We longitudinally characterized the etiology of infectious AGE in children undergoing HCT. Despite the majority of patients meeting the definition for AGE, only half had a pathogen detected, suggesting that differentiating infectious vs. noninfectious AGE (e.g., medication induced) in this population is difficult. Although all subjects with adenovirus and most with sapovirus were symptomatic, asymptomatic C. difficile detection was common. Interestingly, norovirus was not detected. Further investigation of AGE is warranted in this population. Disclosures: All authors: No reported disclosures.